Metaphoric perceptions of individuals with diabetes in Turkey: A content analysis - Aslı Tok Özen; Özlem Bulantekin Düzalan; Betül Yalçın (Belitung Raya Foundation, Indonesia, 2024)
Background: The diagnosis of diabetes mellitus adversely impacts the quality of life due to treatment, changes in daily life, functional disability, and emerging complications. Using metaphors to convey perceptions of diseases and life experiences is crucial for understanding healthcare behaviors. Objective: This study aimed to explore the metaphorical perceptions of “diabetes” and “being a person with diabetes” within a sample group of individuals with diabetes in Turkey. Methods: A qualitative design was employed to investigate the metaphoric perceptions of 72 people with diabetes. Data were collected face-to-face between 15 May and June 2023 using a semi-structured questionnaire. Data were analyzed using content analysis. Results: From the statements of the individuals with diabetes in the sample, seven metaphoric themes related to diabetes – “pain and distress, helplessness and hopelessness, instability, attention and sensitivity, captivity, positive outlook and acceptance, deprivation” – and six metaphoric themes concerning being a person with diabetes – “suffocation and distress, helplessness, powerlessness and disappointment, captivity, attention and sensitivity, guilt, and being worn out” - were identified. Commonly recurring sub-themes with negative connotations included “darkness, well, convict, prison, captivity, microbe, infectious disease, a hot flush, guilt, clouding life, and being ruined.” Some positively framed statements included “friend, traffic sign, and driving a car.” Conclusion: The majority of patients in the study used negative metaphors, with fewer expressing positive sentiments regarding the necessity of accepting and paying attention to the disease. Defining individuals’ metaphorical perceptions of their disease may enable the provision of better quality and holistic care. Nurses, in particular, play a crucial role in facilitating behavioral changes for patients with diabetes to achieve self-management.